Are There Islands of Awareness?. Issue 1 (January 2020) - Bayne, Tim; Seth, Anil K.; Massimini, Marcello
Abstract : Ordinary human experience is embedded in a web of causal relations that link the brain to the body and the wider environment. However, there might be conditions in which brain activity supports consciousness even when that activity is fully causally isolated from the body and its environment. Such cases would involve what we call islands of awareness: conscious states that are neither shaped by sensory input nor able to be expressed by motor output. This Opinion paper considers conditions in which such islands might occur, including ex cranio brains, hemispherotomy, and in cerebral organoids. We examine possible methods for detecting islands of awareness, and consider their implications for ethics and for the nature of consciousness. Highlights: Awareness may persist in fully disconnected cortical islands. We identify both natural and artificial examples of potential islands of awareness. Detecting islands of awareness poses difficult but often addressable challenges. The possibility of islands of awareness raises important ethical and legal issues. The discovery of islands of awareness would have important implications for debates about the nature of consciousness.